New insights into the regulation of Cystathionine beta synthase (CBS), an enzyme involved in intellectual deficiency in Down syndrome - Conan, Pierre; Léon, Alice; Caroff, Noéline; Rollet, Claire; Chaïr, Loubna; Martin, Jennifer; Bihel, Frédéric; Mignen, Olivier; Voisset, Cécile; Friocourt, Gaëlle (Frontiers in Neuroscience, 2023)
Down syndrome (DS), the most frequent chromosomic aberration, results from the presence of an extra copy of chromosome 21. The identification of genes which overexpression contributes to intellectual disability (ID) in DS is important to understand the pathophysiological mechanisms involved and develop new pharmacological therapies. In particular, gene dosage of DYRK1A (Dual specificity tyrosine phosphorylation Regulated Kinase 1A) and of CBS (Cystathionine beta synthase) are crucial for cognitive function. As these two enzymes have lately been the main targets for therapeutic research on ID, we sought to decipher the genetic relationship between them. We also used a combination of genetic and drug screenings using a cellular model overexpressing CYS4, the homolog of CBS in Saccharomyces cerevisiae, to get further insights into the molecular mechanisms involved in the regulation of CBS activity and/or expression. We showed that overexpression of YAK1, the homolog of DYRK1A in yeast, increased CYS4 activity whereas GSK3β was identified as a genetic suppressor of CBS. In addition, analysis of the signalling pathways targeted by the drugs identified through the yeast-based pharmacological screening, and confirmed using human HepG2 cells, emphasized the importance of Akt/GSK3β and NF-κB pathways into the regulation of CBS expression. Taken together, these data provide further understanding into the regulation of CBS and in particular into the genetic relationship between DYRK1A and CBS through the Akt/GSK3β and NF-κB pathways, which should help develop more effective therapies to reduce cognitive deficits in people with DS.